PENGEMBANGAN KURIKULUM, SILABUS DAN SATUAN ACARA PERKULIAHAN (SAP) DI PERGURUAN TINGGI AGAMA ISLAM - Syafruddin Nurdin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2013)
Syllabus is a development of curriculum that contains synopsis, competency, indicator of topic/ sub- topic, and reference of a major. To apply curriculum well in a classroom, it is better to develop syllabus to become a lesson plan. Lesson plan consists of some components; Standard Competency, Basic Comptency, Indicator Competency, Lecture material and its description, learning experience (learning Strategy), media/ learning tools, evaluation system, and reference. Lesson plan is a projection that will be done by lecturer in classroom.Kata kunci: kurikulum, silabus, SAP